Comparison of Automatic and Manual Regression Testing on Mobile Application Health Technology with Black Box Testing Method - Putri, Yoanna Fransisca; Irianto, Aloysius Bagas Pradipta; Sharma, Suman (Indonesian Journal of Information Systems, 2025)
The opening of opportunities for health tech services in Indonesia can lead to increased competition. This makes the company continue to innovate by updating or adding functionality to software systems that have been developed. Because of this, software testing with a shorter time is required so that test performance remains maximum. The object of this research is the Teman diabetes application developed by PT. Global Urban Essentials. In this research, the software testing conducted includes automatic regression testing and manual regression testing. The two testing approaches will be compared to evaluate their effectiveness in detecting bugs and their efficiency in terms of time usage. The method used in automatic regression testing is the black box testing method, implemented within the Software Testing Life Cycle (STLC) that is include requirement analysis, test planning, test case development, test environment setup, and test execution. The primary focus of this research is to asses the effectiveness of automatic and manual regression testing in identifying bugs/errors and measuring efficiency in time utilization, based on the analysis of test reports generated from both methods. In this study, it was found that testing carried out by automation is 9.77% faster. In addition, a bug was found in the shopping feature as a result of the new features being released. This bug was discovered after running automated regression testing and was not found in manual regression testing because the bug testing was missed.